1998
DOI: 10.1084/jem.188.12.2277
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Mice with Urease Vaccine Affords Protection against Helicobacter pylori Infection in the Absence of Antibodies and Is Mediated by MHC Class II–restricted Responses

Abstract: We examined the roles of cell- and antibody-mediated immunity in urease vaccine–induced protection against Helicobacter pylori infection. Normal and knockout mice deficient in major histocompatibility complex (MHC) class I, MHC class II, or B cell responses were mucosally immunized with urease plus Escherichia coli heat-labile enterotoxin (LT), or parenterally immunized with urease plus aluminum hydroxide or a glycolipid adjuvant, challenged with H. pylori strain X47-2AL, and H. pylori organisms and leukocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
315
3
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(356 citation statements)
references
References 46 publications
34
315
3
4
Order By: Relevance
“…Other workers have reported increased gastric neutrophil infiltration in vaccinated mice [28,38]and it has not been clarified whether this represents a mechanism or a byproduct of the inflammatory response. Velin et al reported that depletion of neutrophils had no effect on protection in vaccinated mice challenged with H. felis [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other workers have reported increased gastric neutrophil infiltration in vaccinated mice [28,38]and it has not been clarified whether this represents a mechanism or a byproduct of the inflammatory response. Velin et al reported that depletion of neutrophils had no effect on protection in vaccinated mice challenged with H. felis [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, the key role of Th1 cells in inducing the secretion of IgG by activated plasma cells or the activation of macrophage killing appear to be dispensable for protection [37][38][39]. Immunity might be facilitated by as yet unknown effector mechanisms and it is important to explore novel cell types or molecules in immunity to this end.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study IL-18 Ϫ/Ϫ mice exhibited a reduction in splenic as well as gastric IFN-␥ production. We and others have documented that well-protected WT mice have increased numbers of CD4 ϩ T cells infiltrating the gastric mucosa (6,8,18,47,48). Therefore, one would hypothesize that local production of IFN-␥ is a key element in T cell-mediated protection against H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the fact that post-immunization gastritis, seen in well-protected mice, is usually correlated with a strong local IgG response in the gastric mucosa (24) reveals the unfavorable effect of humoral immunity against H. pylori. In addition, it has been shown that H. pylori-specifi c circulating antibodies failed to protect against H. pylori infection (9). Moreover, B-cell defi cient mice were fully protected by challenging with H. pylori (3).…”
Section: Methodsmentioning
confidence: 99%